2017
DOI: 10.1177/0300060517729907
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of invasive pulmonary aspergillosis in patients with liver failure: Clinical presentation, risk factors, and outcomes

Abstract: ObjectiveInvasive pulmonary aspergillosis (IPA) is a severe and often lethal infection. The possible risk factors, clinical presentation, and treatment of patients with simultaneous liver failure and IPA have received little attention in previous studies. The aim of this study was to investigate the epidemiology of IPA in patients with liver failure in an effort to reduce patient mortality.MethodsThe patients with liver failure (including acute liver failure , sub-acute liver failure , acute-on-chronic liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Critically ill patients experiencing liver failure are also at risk for aspergillosis, as shown by Zhang et al 62 with an incidence of 5% of IPA in this setting. Steroids, antibiotics, and hepatorenal syndrome are frequent under this condition and each one is an independent risk factor for IPA in this population.…”
Section: Liver Failurementioning
confidence: 91%
“…Critically ill patients experiencing liver failure are also at risk for aspergillosis, as shown by Zhang et al 62 with an incidence of 5% of IPA in this setting. Steroids, antibiotics, and hepatorenal syndrome are frequent under this condition and each one is an independent risk factor for IPA in this population.…”
Section: Liver Failurementioning
confidence: 91%
“…Several studies have been conducted in intensive care units and identified, in the absence of malignancy, HSCT, or solid organ transplantations, the following risk factors for IA: severe chronic obstructive pulmonary disease, steroid therapy, HIV infection, influenza virus infection (especially H1N1), chronic renal replacement therapy, liver failure, near-drowning, prolonged period of mechanical ventilator dependency. 25,[97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Irrespective of these comorbidities, immune paralysis (also called compensatory antiinflammatory response syndrome) induced by severe sepsis can by itself be a risk factor for IA. 114,115 Recently several cases of IA have been reported in patients suffering from severe fever with thrombocytopenia syndrome virus infection, a tick-born disease present in China, Korea, Vietnam, and Japan.…”
Section: Critically Ill Patientsmentioning
confidence: 99%
“…HIV/AIDS and dementia, diagnoses included within the CCI, were consistently the least occurring comorbidities across the cohorts. Although HIV/AIDS have been documented as a significant comorbidity in immunocompromised patients and liver failure patients, 30 , 31 they may be underrepresented in the Optum commercial dataset. Finally, CCI cohort demonstrated higher comorbidity burdens for patients developing invasive mold infections, indicating higher mortality and/or higher resource use at the outset.…”
Section: Discussionmentioning
confidence: 99%